The first Ukrainian centre of hand surgery is 30 years old - Loskutov, Oleksandr; Beliy, Sergey; Naumenko, Leonid (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
The article deals with the history of the opening of the first hand surgery centre in Ukraine. The part played in its foundation by Prof. Kolontay Yu.Yu. is described. Landmarks in the development of the Centre and the contribution of its staff into the formation of hand surgery in Ukraine are specified.